Reenvisioning Cytotoxic Lesions of Corpus Callosum in Light of Coronavirus Disease-2019: Review with Related Concepts - Udit Chauhan; Khanak K. Nandolia; Rahul Dev (Journal of Medical Evidence)
Cytotoxic lesions of the corpus callosum (CLOCC) describe secondary reversible entities, infections being the forerunner aetiology, with metabolic forming another subset. Coronavirus disease-2019 (COVID-19) infection highlighted CLOCC due to its frequent occurrence in infected and post-vaccinated individuals. Cytokine-mediated response, with contribution from other pathways, affected particularly vulnerable splenium of the corpus callosum. Clinical presentation was typical of neurological affliction, including visual and auditory pathway involvement. Scattered cases of atypical neurological and other system involvement were seen. Magnetic resonance imaging (MRI) showed characteristic imaging findings, associated white matter and other changes. Complete recovery was the norm, with few exceptions. This study aimed to review pathogenesis, neurological and imaging manifestations of CLOCC concerning various aetiologies and differentials, the forerunner being COVID-19, and highlight a few instances of atypical presentation. Authors searched the PubMed database for articles published in the Last 5 Years using the keywords ‘Cytotoxic lesions of corpus callosum COVID-19 MRI’. Articles explaining pathogenesis, clinical symptomatology and imaging findings were included, with few articles depicting atypical neurological and imaging findings. Well-defined altered signal intensity lesion in the corpus callosum, showing diffusion restriction, confined to splenium in the majority. Involvement of the rest of the corpus callosum adjoining cerebral white matter is seen in a few cases with enhancement and haemorrhage. Neurological symptoms were dominant, with adjunct abdominal manifestations in a few. Complete clinical and imaging resolution was the norm in the vast majority.